2016
DOI: 10.1042/cs20160002
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial health, the epigenome and healthspan

Abstract: Food nutrients and metabolic supply-demand dynamics constitute environmental factors that interact with our genome influencing health and disease states. These gene–environment interactions converge at the metabolic-epigenome-genome axis to regulate gene expression and phenotypic outcomes. Mounting evidence indicates that nutrients and lifestyle strongly influence genome-metabolic functional interactions determining disease via altered epigenetic regulation. The mitochondrial network is a central player of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 231 publications
1
47
0
Order By: Relevance
“…32 Therefore, we hypothesize that polyP might affect the mitochondrial ATP metabolism, such as ATP synthase activity, ATPase activity, and adenylate kinase activity. PolyP also plays an essential role in mitochondrial ion transport by regulating the mPTP, 33 while mPTP opening is strongly associated with cell death. 34 Furthermore, Elustondo et al 23 reported that the composition of the ATPase C-subunit, polyhydroxybutyrate, and polyP is required for the mPTP opening.…”
Section: Discussionmentioning
confidence: 99%
“…32 Therefore, we hypothesize that polyP might affect the mitochondrial ATP metabolism, such as ATP synthase activity, ATPase activity, and adenylate kinase activity. PolyP also plays an essential role in mitochondrial ion transport by regulating the mPTP, 33 while mPTP opening is strongly associated with cell death. 34 Furthermore, Elustondo et al 23 reported that the composition of the ATPase C-subunit, polyhydroxybutyrate, and polyP is required for the mPTP opening.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial metabolites can serve as substrates for reactions that modify DNA [4]. In addition, biomolecules whose abundance or redox status respond to mitochondrial activity can serve as metabolic sensors for nuclear chromatin responses [4].…”
Section: The Nuclear Epigenome In Retrograde Signalingmentioning
confidence: 99%
“…In addition, biomolecules whose abundance or redox status respond to mitochondrial activity can serve as metabolic sensors for nuclear chromatin responses [4]. These metabolites and “energy sensors” are essential for cross-compartment communication, so much so that some hypothesize an ancient evolutionary origin of these mechanisms [1].…”
Section: The Nuclear Epigenome In Retrograde Signalingmentioning
confidence: 99%
See 2 more Smart Citations